ANALISIS TEKANAN HIDROLIK TERHADAP OIL LOSSES PADA MESIN PRESS KAPASITAS 15 TON - Tarigan, Daniel Elieser; Zuliantoni; Bismantolo, Putra (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2025)
In palm oil processing, there are five main stages: sterilization, threshing, digestion, pressing, and clarification. Among these, the pressing stage is one of the most critical. The pressing machine is used to separate crude oil from the fibers in the fruit pulp. This machine includes a pressing component, commonly referred to as the cone cage, which is operated by a hydraulic mechanism. The palm oil pressing process plays a crucial role in determining the success of processing fresh fruit bunches (FFB), as significant oil losses often occur during this stage. One of the key factors affecting these losses is the value of the hydraulic pressure. This study aims to investigate the effect of hydraulic pressure on oil losses in fibers for each pressing machine and to understand how the pressing machine operates. To analyze the hydraulic pressure variable and oil losses in fibers, observations were conducted by monitoring the pressure gauge on each pressing machine. The oil losses in fibers were measured through laboratory testing at the factory. The collected data were then compared. The results of this study indicate that hydraulic pressure has a significant effect on oil losses in the fibers of the pressing machine. At a hydraulic pressure of 49 bar, the smallest oil loss was recorded at 3.28%, whereas at a hydraulic pressure of 40 bar, the highest oil loss was observed at 4.42%. This demonstrates that higher hydraulic pressure results in lower oil losses, and vice versa.